Pengaruh Strategi Mastery Learning Terhadap Kemampuan Pemecahan Masalah Siswa di SD Negeri 4 Lintang Kanan - Nike Netriani; Kharisma Pratidina (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Improving the quality of education, of course, is inseparable from the teaching and learning process as the main activity in schools, Mathematics is one of the very important branches of science that is taught at every level of education starting from elementary school (SD) to high school (SMA), there is also this research carried out at SD Negeri 4 Lintang Kanan in grade 5, The purpose of this study is to have a positive influence by using the Mastery Learning Strategy in Mathematics lessons with measurement materials, time distance and speed, this research was carried out after seeing pre-cycle observations that obtained incomplete score results due to lack of concentration from students who were still less active and playing games in learning, and learning was still monotonous, after cycle 1 and cycle 2 the students' grades became complete With an average score of 78 indigo, this study uses observation sheets, and a written essay test to obtain accurate data.